10-K Disclosure of Corporate Social Responsibility and Firms' Competitive Advantages. Issue 1 (1st January 2020) - Cannon, James N.; Ling, Zhejia; Wang, Qian; Watanabe, Olena V.
Abstract : In this paper, we offer evidence that disclosure of corporate social responsibility (CSR) in the 10-K provides information about firms' competitive advantages. We create a textual measure of CSR disclosure that aggregates CSR keywords found in 10-Ks. We measure firms' competitive advantages by using levels of and persistence of industry-adjusted gross margin; selling, general, and administrative (SG&A) margin; and operating margin. We first show that 10-K CSR disclosure intensity is associated with lower levels of gross margin but higher SG&A margin. We then observe that firms with more CSR keywords in their 10-Ks maintain more persistent above-industry-median gross and operating margins. Upon sorting our full set of 10-K CSR keywords into three subcategories (philanthropy, business practice, and product), we find that the intensities of disclosure in these CSR subcategories have associations with varying competitive advantages.